Peran Learning Organization Dalam Meningkatkan Kinerja Pegawai Dinas Pendidikan Dan Kebudayaan Kota Cilegon - Suhendra, Suhendra; Hayadi, Bambang Herawan (Peneliti.net, 2024)
Human resources are considered as dynamic resources. Performance is a very important element in the progress of an organization. The purpose of this study was to determine the role of learning organization in improving the performance of the employees in Dinas Pendidikan dan Kebudayaan Kota Cilegon. This study using a descriptive type of research with a qualitative approach. The population and sample are employees of Dinas Pendidikan dan Kebudayaan Kota Cilegon Regency. The results obtained are Learning Organizations play a role in improving the performance of employees of Dinas Pendidikan dan Kebudayaan Kota Cilegon, due to training and guidance from superiors so as to improve employee performance. This means that the higher the role of the Learning Organization will improve employee performance